Education of Religious Harmony in Surah At-Tin: A Study of Al-Qasimi's Thought - Fatah, Nasrul; Syarifah Laili; Wira Lestari; Hasan (Westscience Press, 2025)
This article examines the hints of religious harmony in Surah At-Tin through a thematic interpretation approach to the classic tafsir work Mahasin At-Ta'wil by Jamaluddin Al-Qasimi. In his tafsir, Al-Qasimi not only focuses on theological aspects, but also emphasizes universal human values and justice. These values become a relevant foundation in building interfaith harmony in a multicultural society. This study found that Al-Qasimi interpreted this letter as a form of respect for humans as noble and morally responsible creatures, as well as a call to uphold justice without discrimination on the basis of religious beliefs.